Anti-leptospirose agglutinins in equine sera, from São Paulo, Goias, and Mato Grosso do Sul, Brazil, 1996-2001 - Langoni, H. [UNESP] (2004)
Equine leptospirosis can present a non-symptomatic form, an acute clinical form, or even develop chronically, causing reproductive alterations, such as abortion and recurrent uveitis. Since the prevalence of leptospirosis in several countries and regions is widely reported, the objective of this study was to verify the prevailing equine leptospirosis in different regions of Brazil. Sera from 1402 blood samples from horses of different age, sex, breed, and purpose were examined. These samples came from southeastern and central west states of Brazil. The method utilized was the Microscopic Agglutination Test (MAT), with 12 different Leptospira serovars. From the sera tested, 754 (54%) were positive for one (385) or more (372) serovars. These results were higher when compared to national and international levels. The most commonly found serovars were icterohaemorrhagiae (37.01%), suggesting exposure to rodents, castellonis (16.97%), and djasiman (15.19%). There were significant differences of reagents between sexes, and a tendency toward higher positivity with age. Distribution of sera-reagents related to aptitude showed a markedly higher value for work animals than for sporting ones. Higher rates were found for animals with undefined breed. There were no significant differences related to regional origin. As an indication of multiple exposure, significant associations were observed between the following serovars: castellonis and djasiman; castellonis and grippotyphosa; castellonis and copenhageni; castellonis and icterohaemorrhagiae; castellonis and pomona; canicola and pomona; canicola and djasiman; djasiman and copenhageni; icterohaemorrhagiae and djasiman; icterohaemorrhagiae and pyrogenes; copenhageni and pomona. These results showed the necessity of further studies on the epidemiology of this disease in equines and its relationship to human illness.